A low-temperature rapid solid-state synthesis method of a high-crystallinity Na2Fe2(SO4)3 positive electrode material

CN122968209APending Publication Date: 2026-10-23SUZHOU NACHU NEW ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611283878.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但实际中颗粒粒径分布宽、杂相多、结晶度不足的问题仍然普遍

Benefits of technology

[0032]1、本方法制备得到的Na2Fe2(SO4)3 粉末结晶度显著提升,且颗粒平均直径可控制在 <500 nm 级别。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968209A_ABST
    Figure CN122968209A_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature rapid solid-state synthesis method of a high-crystallinity Na2Fe2(SO4)3 positive electrode material and relates to the technical field of sodium ion battery positive electrode material preparation. FeSO4, Na2SO4 and a fluxing agent are ball milled according to a certain mass fraction ratio, are rapidly heated and are kept at temperature according to a procedure in an inert atmosphere, are then washed with ethanol, are dried, are treated at high temperature for the second time, and finally, nanoscale high-crystallinity Na2Fe2(SO4)3 active powder is obtained. The prepared material has the advantages of particle refinement, increased specific surface area, and significantly improved electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery cathode material preparation technology, and in particular to a low-temperature rapid solid-state synthesis method for highly crystalline Na2Fe2(SO4)3 cathode material. Background Technology

[0002] With the continuous expansion of application scenarios such as large-scale energy storage of new energy sources, grid connection of renewable energy, and vehicle electrification, traditional lithium-ion battery technology, although widely commercialized, has also exposed problems such as uneven distribution of raw material lithium resources, rising prices, environmental and safety risks, and cost sensitivity in large-scale energy storage. Therefore, sodium-ion batteries (SIBs), energy storage systems based on sodium (Na) ions, have attracted increasing research attention due to their abundant raw material resources, lower cost potential, and relatively better safety.

[0003] In the field of sodium-ion battery cathode materials, researchers have found that although sodium ions have a larger radius, are more difficult to migrate, and present greater challenges in structural stability and volume change suppression compared to lithium ions, good performance can still be achieved through material design. In particular, polyanionic compounds (such as sulfates, phosphates, and pyrophosphates) as cathode materials, due to the strong induced electronegativity of their sulfate (SO4²⁻) or phosphate (PO4³⁻) groups, help to improve the operating voltage of the cathode.

[0004] Among these materials, Na2Fe2(SO4)3 (sodium-ferric sulfate) has attracted attention as a cathode candidate material with an Alluaudite-type framework structure due to its high Fe³⁺ / Fe²⁺ reaction potential (about 3.8 V) and high theoretical capacity.

[0005] For example, in a 2019 paper published by Jungers et al., a stoichiometric amount of Na2Fe2(SO4)3 was successfully synthesized in an organic medium using a "reverse-strike coprecipitation" strategy. They pointed out that the sulfate-induced effect enabled the material to exhibit a high operating voltage during sodium ion insertion / extraction.

[0006] However, despite the promising prospects of sodium ferric sulfate materials such as Na2Fe2(SO4)3, there are still many technical bottlenecks in their practical preparation and application, mainly including:

[0007] The material synthesis process is complex and costly: many current studies use methods such as wet chemical precipitation, high-temperature ball milling / solid sintering, which involve high sintering temperature, long holding time, large amount of flux or coating agent, and high difficulty in conductivity modification, making it difficult to achieve large-scale low-cost production.

[0008] Poor material conductivity and low packing density: Although the sulfate structure brings the advantage of high voltage, its framework itself has low conductivity, requiring additional carbon coating or conductive network reinforcement; in addition, the powder packing density is usually not high, which affects the volumetric energy density of the electrode.

[0009] Controlling particle size and structure is challenging: To achieve excellent rate performance and cycling stability, it is necessary to reduce the particle size to the nanometer or sub-nanometer scale, increase crystallinity, and suppress the formation of impurity phases. However, in practice, problems such as wide particle size distribution, numerous impurity phases, and insufficient crystallinity are still common.

[0010] Stability and compatibility issues: Sulfate materials may undergo hydration, structural expansion, or decomposition in air or water-containing environments; in battery systems, factors such as electrolyte compatibility, structural decay during cycling, and volume changes during sodium removal / return also affect practical application.

[0011] To address the aforementioned issues, relevant patents have proposed technical solutions such as modified coating, structural composites, enhanced conductivity, low-temperature synthesis, and large-scale equipment. For example, patent CN 106 058 251 B (“A sodium-ion battery cathode Na2Fe2(SO4)3@alumina composite material and its preparation method”) discloses a Na2Fe2(SO4)3@Al2O3 core-shell structure material and its preparation method, improving stability through a thin layer of alumina coating. Another example is patent CN 105 355 886 A (“A sodium-ion battery cathode Na2+2xFe2-x(SO4)3@carbon composite material and its preparation method”), which proposes methods for carbon composite coating and nanoparticle size control. Yet another example is patent WO 2024 422016 A1 (“A sodium iron sulfate cathode material and its preparation method and application”), which further proposes solutions such as amphiphilic molecule modification and interface engineering to improve the electrochemical performance of the material.

[0012] There is still an urgent need for a simpler, lower-cost, and more scalable method to prepare Na2Fe2(SO4)3 or its modified system that can achieve high crystallinity, fine particles, excellent conductivity and cycle stability, so as to promote the industrial application of this type of polyanionic sodium iron sulfate cathode material in sodium-ion batteries. Summary of the Invention

[0013] Based on the problems raised in the background technology mentioned above, this invention proposes a low-temperature rapid solid-state synthesis method for highly crystalline Na2Fe2(SO4)3 cathode materials.

[0014] The technical solution is as follows:

[0015] A low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material includes the following steps, in parts by mass:

[0016] (1) Mix 80-100 parts of anhydrous ferrous sulfate, 80-100 parts of sodium sulfate and 50-120 parts of fluxing salt by mass to obtain a mixture;

[0017] (2) Under the protection of inert gas, add 50-95 parts of solvent and 2-5 parts of crystallization aid to the mixture in step (1), add ball milling beads and perform wet ball milling for 2-6 hours and 200-500 r / min.

[0018] (3) The ball-milled mixture is loaded into a graphite crucible and heated and held in an inert gas according to the following temperature program: 200±10℃ for 2 h~3 h, then heated to 350±10℃ for 1 h±0.5 h, then heated to 450±10℃ for 8 h~12 h, then heated to 550±10℃ for 1 h~3 h, and then naturally cooled to room temperature;

[0019] (4) Wash the powder obtained in step (3) twice with ethanol, each time using 2 to 5 times the mass of the powder, filter and dry to obtain the dry precursor powder.

[0020] (5) Place the dried precursor powder in an inert gas, add 5 to 10 parts of amorphous carbon and mix evenly, heat to 600±10℃ and keep warm for 3 to 5 hours, then cool to room temperature to obtain the final highly crystalline Na2Fe2(SO4)3 active powder.

[0021] In some embodiments, the purity of the anhydrous ferrous sulfate and sodium sulfate is not less than 99.0%.

[0022] In some embodiments, the fluxing salt mixture is prepared in a mass ratio of LiCl:KCl = 1:1.

[0023] In some embodiments, the inert gas is Ar or He, and the flow rate is 100–300 mL / min.

[0024] In some embodiments, the solvent is ethanol, acetone, ethylene glycol, or N-methylpyrrolidone.

[0025] In some embodiments, the crystallization aid is selected from the addition product of 4-propenylthioaminourea (CAS: 3766-55-0) and allyl mercaptan under the action of ethylenediamine, and its preparation method is as follows:

[0026] A1: According to the mass fraction, add 60-90 parts of 4-propenylthioaminourea (CAS: 3766-55-0) and 400-600 parts of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 35-45℃, and add 2-4 parts of ethylenediamine (CAS: 107-15-3) as a catalyst;

[0027] A2: Slowly add 40-60 parts of allyl mercaptan (CAS: 870-23-5) dropwise over a time of 0.5-1 h, while maintaining a stirring speed of 150-200 rpm and keeping the mixture at 35-45 °C for 4-5 h. After the reaction is complete, evaporate the mixture under reduced pressure to half its original volume, cool it to room temperature, and allow it to crystallize for 12-16 h. Filter and collect the crystals, then vacuum dry them at 70-90 °C for 3-4 h to obtain the target crystallization aid.

[0028] In some embodiments, the mass ratio of the grinding beads to the mixture is 10:1 to 30:1.

[0029] In some embodiments, the drying temperature is 120±10℃ and the time is 6 h to 12 h.

[0030] In some embodiments, the amorphous carbon is selected from petroleum coking residue, coal coking residue, asphalt coking residue, lignin carbonization residue, or corn stalk carbonization residue.

[0031] Technical effects:

[0032] 1. The crystallinity of Na2Fe2(SO4)3 powder prepared by this method is significantly improved, and the average particle diameter can be controlled at the level of <500 nm.

[0033] 2. As a positive electrode material in sodium-ion batteries, it exhibits higher initial reversible capacity, better rate performance, and longer cycle life.

[0034] 3. Compared with the traditional high-temperature long-time sintering method, the synthesis cycle is shortened, energy consumption is reduced, and efficiency is improved.

[0035] 4. The process is simple, has good repeatability, and is more suitable for large-scale production. Attached Figure Description

[0036] Figure 1 This is a scanning electron microscope image of Example 2. Detailed Implementation

[0037] The following are specific embodiments, which describe the contents disclosed in this application in more detail. These embodiments are merely illustrative, as various modifications and changes will be apparent to those skilled in the art within the scope of the disclosure of this application.

[0038] Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0039] Example 1: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0040] 1. Experimental Materials

[0041] Anhydrous ferrous sulfate (80g, purity ≥99.0%), sodium sulfate (80g, purity ≥99.0%), fluxing salt mixture (LiCl 25g + KCl 25g, mass ratio 1:1), solvent (ethanol 50g), crystallization aid raw materials (4-propenylthioaminourea 60g, anhydrous ethanol 400g, ethylenediamine 2g, allyl mercaptan 40g), amorphous carbon (petroleum coking residue 5g), ball milling beads, Ar gas, ethanol (for washing), graphite crucible.

[0042] 2. Experimental Procedure

[0043] (1) Preparation of mixture

[0044] 80g of anhydrous ferrous sulfate, 80g of sodium sulfate and 50g of fluxing salt (LiCl and KCl mixed by mass) are thoroughly mixed to obtain a uniform mixture.

[0045] (2) Wet ball milling treatment

[0046] 1. Preparation of crystallization aids:

[0047] A1: Add 60g of 4-propenylthioaminourea and 400g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 35℃, and add 2g of ethylenediamine as a catalyst.

[0048] A2: Slowly add 40g of allyl mercaptan over a period of 0.5h, maintain the stirring speed at 150rpm, and keep the reaction at 35℃ for 4h. After the reaction is complete, evaporate under reduced pressure to concentrate to half of the original volume, cool to room temperature and let it stand to crystallize for 12h. Filter and collect the crystals, and dry them under vacuum at 70℃ for 3h to obtain the crystallization aid.

[0049] 2. Ball milling: Under Ar gas protection, add 50g of ethanol and 2g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 10:1), place it in a ball mill for wet ball milling, set the rotation speed to 200r / min, and the ball milling time to 2h.

[0050] (3) Segmented heating and roasting

[0051] The ball-milled mixture was placed into a graphite crucible, and Ar gas (flow rate 100 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 190℃ (200±10℃) and held for 2 hours, then raised to 340℃ (350±10℃) and held for 0.5 hours, then raised to 440℃ (450±10℃) and held for 8 hours, and finally raised to 540℃ (550±10℃) and held for 1 hour. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0052] (4) Washing and drying

[0053] The calcined powder obtained in step (3) was washed twice with ethanol, each time using twice the amount of ethanol as the powder mass; after filtration, the precipitate was placed in an oven and dried at 110℃ (120±10℃) for 6 hours to obtain the dried precursor powder.

[0054] (5) Carbon mixing and high-temperature treatment

[0055] The dried precursor powder was placed under Ar gas protection, and 5g of petroleum coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 590℃ (600±10℃) and kept at that temperature for 3h. The mixture was then cooled to room temperature to obtain highly crystalline Na2Fe2(SO4)3 active powder.

[0056] Example 2: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0057] 1. Experimental Materials

[0058] Anhydrous ferrous sulfate (90g, purity ≥99.0%), sodium sulfate (90g, purity ≥99.0%), fluxing salt mixture (LiCl 35g + KCl 35g, mass ratio 1:1), solvent (acetone 65g), crystallization aid raw materials (4-propenylthioaminourea 70g, anhydrous ethanol 480g, ethylenediamine 3g, allyl mercaptan 48g), amorphous carbon (coal coking residue 7g), ball milling beads, He gas, ethanol (for washing), and graphite crucible.

[0059] 2. Experimental Procedure

[0060] (1) Preparation of mixture

[0061] 90g of anhydrous ferrous sulfate, 90g of sodium sulfate and 70g of fluxing salt (LiCl and KCl mixed by mass) were thoroughly mixed to obtain a uniform mixture.

[0062] (2) Wet ball milling treatment

[0063] 1. Preparation of crystallization aids:

[0064] A1: Add 70g of 4-propenylthioaminourea and 480g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 38℃, and add 3g of ethylenediamine as a catalyst.

[0065] A2: Slowly add 48g of allyl mercaptan over a period of 0.7h, while maintaining a stirring rate of 170rpm and keeping the mixture at 38℃ for 4.2h. After the reaction is complete, evaporate the mixture under reduced pressure to half its original volume, cool it to room temperature and allow it to crystallize for 13h. Filter and collect the crystals, then vacuum dry them at 75℃ for 3.2h to obtain the crystallization aid.

[0066] 2. Ball milling: Under He gas protection, add 65g of acetone and 3g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 18:1), place it in a ball mill for wet ball milling, set the rotation speed to 300r / min, and the ball milling time to 3.5h.

[0067] (3) Segmented heating and roasting

[0068] The ball-milled mixture was placed into a graphite crucible, and He gas (flow rate 180 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 200℃ (200±10℃) and held for 2.3 h, then raised to 350℃ (350±10℃) and held for 1 h, then raised to 450℃ (450±10℃) and held for 9 h, and finally raised to 550℃ (550±10℃) and held for 1.8 h. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0069] (4) Washing and drying

[0070] The calcined powder obtained in step (3) was washed twice with ethanol, each time using 3 times the mass of the powder; after filtration, the precipitate was placed in an oven and dried at 120℃ (120±10℃) for 8 hours to obtain the dried precursor powder.

[0071] (5) Carbon mixing and high-temperature treatment

[0072] The dried precursor powder was placed under He gas protection, and 7g of coal coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 600℃ (600±10℃) and kept at that temperature for 3.5h. After cooling to room temperature, highly crystalline Na2Fe2(SO4)3 active powder was obtained.

[0073] Example 3: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0074] 1. Experimental Materials

[0075] Anhydrous ferrous sulfate (95g, purity ≥99.0%), sodium sulfate (95g, purity ≥99.0%), fluxing salt mixture (LiCl 50g + KCl 50g, mass ratio 1:1), solvent (ethylene glycol 80g), crystallization aid raw materials (4-propenylthioaminourea 80g, anhydrous ethanol 550g, ethylenediamine 3.5g, allyl mercaptan 55g), amorphous carbon (asphalt coking residue 8.5g), grinding beads, Ar gas, ethanol (for washing), graphite crucible.

[0076] 2. Experimental Procedure

[0077] (1) Preparation of mixture

[0078] 95g of anhydrous ferrous sulfate, 95g of sodium sulfate and 100g of fluxing salt (LiCl and KCl mixed by mass) were thoroughly mixed to obtain a uniform mixture.

[0079] (2) Wet ball milling treatment

[0080] 1. Preparation of crystallization aids:

[0081] A1: Add 80g of 4-propenylthioaminourea and 550g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 42℃, and add 3.5g of ethylenediamine as a catalyst;

[0082] A2: Slowly add 55g of allyl mercaptan over a period of 0.9h, maintain the stirring speed at 190rpm, and keep the reaction at 42℃ for 4.5h. After the reaction is complete, evaporate under reduced pressure to concentrate to half of the original volume, cool to room temperature and let it stand to crystallize for 15h, filter and collect the crystals, and dry them under vacuum at 85℃ for 3.5h to obtain the crystallization aid.

[0083] 2. Ball milling: Under Ar gas protection, add 80g of ethylene glycol and 4g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 25:1), place it in a ball mill for wet ball milling, set the speed to 400r / min, and the ball milling time to 5h.

[0084] (3) Segmented heating and roasting

[0085] The ball-milled mixture was placed into a graphite crucible, and Ar gas (flow rate 250 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 205℃ (200±10℃) and held for 2.7 h, then raised to 355℃ (350±10℃) and held for 1.3 h, then raised to 455℃ (450±10℃) and held for 11 h, and finally raised to 560℃ (550±10℃) and held for 2.5 h. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0086] (4) Washing and drying

[0087] The calcined powder obtained in step (3) was washed twice with ethanol, each time using 4 times the mass of the powder; after filtration, the precipitate was placed in an oven and dried at 125℃ (120±10℃) for 10h to obtain the dried precursor powder.

[0088] (5) Carbon mixing and high-temperature treatment

[0089] The dried precursor powder was placed under Ar gas protection, and 8.5g of asphalt coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 605℃ (600±10℃) and held for 4.2h. After cooling to room temperature, highly crystalline Na2Fe2(SO4)3 active powder was obtained.

[0090] Example 4: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0091] 1. Experimental Materials

[0092] Anhydrous ferrous sulfate (100g, purity ≥99.0%), sodium sulfate (100g, purity ≥99.0%), fluxing salt mixture (LiCl 60g + KCl 60g, mass ratio 1:1), solvent (N-methylpyrrolidone 95g), crystallization aid raw materials (4-propenylthioaminourea 90g, anhydrous ethanol 600g, ethylenediamine 4g, allyl mercaptan 60g), amorphous carbon (corn stalk carbonization residue 10g), grinding beads, He gas, ethanol (for washing), graphite crucible.

[0093] 2. Experimental Procedure

[0094] (1) Preparation of mixture

[0095] 100g of anhydrous ferrous sulfate, 100g of sodium sulfate and 120g of fluxing salt (LiCl and KCl mixed by mass) are thoroughly mixed to obtain a uniform mixture.

[0096] (2) Wet ball milling treatment

[0097] 1. Preparation of crystallization aids:

[0098] A1: Add 90g of 4-propenylthioaminourea and 600g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 45℃, and add 4g of ethylenediamine as a catalyst.

[0099] A2: Slowly add 60g of allyl mercaptan over a period of 1 hour, while maintaining a stirring speed of 200 rpm and keeping the mixture at 45°C for 5 hours. After the reaction is complete, evaporate the mixture under reduced pressure to half its original volume, cool it to room temperature, and allow it to stand for 16 hours to crystallize. Filter and collect the crystals, then dry them under vacuum at 90°C for 4 hours to obtain the crystallization aid.

[0100] 2. Ball milling: Under He gas protection, add 95g of N-methylpyrrolidone and 5g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 30:1), place it in a ball mill for wet ball milling, set the speed to 500r / min, and the ball milling time to 6h.

[0101] (3) Segmented heating and roasting

[0102] The ball-milled mixture was placed into a graphite crucible, and He gas (flow rate 300 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 210℃ (200±10℃) and held for 3 hours, then raised to 360℃ (350±10℃) and held for 1.5 hours, then raised to 460℃ (450±10℃) and held for 12 hours, and finally raised to 570℃ (550±10℃) and held for 3 hours. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0103] (4) Washing and drying

[0104] The calcined powder obtained in step (3) was washed twice with ethanol, each time using 5 times the mass of the powder; after filtration, the precipitate was placed in an oven and dried at 130℃ (120±10℃) for 12h to obtain the dried precursor powder.

[0105] (5) Carbon mixing and high-temperature treatment

[0106] The dried precursor powder was placed under He gas protection, and 10g of corn stalk carbonization residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 610℃ (600±10℃) and kept at that temperature for 5h. After cooling to room temperature, highly crystalline Na2Fe2(SO4)3 active powder was obtained.

[0107] Comparative Example 1: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0108] 1. Experimental Materials

[0109] Anhydrous ferrous sulfate (80g, purity ≥99.0%), sodium sulfate (80g, purity ≥99.0%), fluxing salt mixture (LiCl 25g + KCl 25g, mass ratio 1:1), solvent (ethanol 50g), amorphous carbon (petroleum coking residue 5g), ball milling beads, Ar gas, ethanol (for washing), graphite crucible.

[0110] 2. Experimental Procedure

[0111] (1) Preparation of mixture

[0112] 80g of anhydrous ferrous sulfate, 80g of sodium sulfate and 50g of fluxing salt (LiCl and KCl mixed by mass) are thoroughly mixed to obtain a uniform mixture.

[0113] (2) Wet ball milling treatment

[0114] Ball milling: Under Ar gas protection, add 50g of ethanol to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 10:1), place it in a ball mill for wet ball milling, set the speed to 200r / min, and the ball milling time to 2h.

[0115] (3) Segmented heating and roasting

[0116] The ball-milled mixture was placed into a graphite crucible, and Ar gas (flow rate 100 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 190℃ (200±10℃) and held for 2 hours, then raised to 340℃ (350±10℃) and held for 0.5 hours, then raised to 440℃ (450±10℃) and held for 8 hours, and finally raised to 540℃ (550±10℃) and held for 1 hour. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0117] (4) Washing and drying

[0118] The calcined powder obtained in step (3) was washed twice with ethanol, each time using twice the amount of ethanol as the powder mass; after filtration, the precipitate was placed in an oven and dried at 110℃ (120±10℃) for 6 hours to obtain the dried precursor powder.

[0119] (5) Carbon mixing and high-temperature treatment

[0120] The dried precursor powder was placed under Ar gas protection, and 5g of petroleum coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 590℃ (600±10℃) and kept at that temperature for 3h. The mixture was then cooled to room temperature to obtain highly crystalline Na2Fe2(SO4)3 active powder.

[0121] Comparative Example 2: Low-Temperature Rapid Solid-State Synthesis of Highly Crystalline Na2Fe2(SO4)3 Cathode Material

[0122] 1. Experimental Materials

[0123] Anhydrous ferrous sulfate (80g, purity ≥99.0%), sodium sulfate (80g, purity ≥99.0%), fluxing salt mixture (LiCl 25g + KCl 25g, mass ratio 1:1), solvent (ethanol 50g), crystallization aid raw materials (anhydrous ethanol 400g, ethylenediamine 2g, allyl mercaptan 40g), amorphous carbon (petroleum coking residue 5g), grinding beads, Ar gas, ethanol (for washing), graphite crucible.

[0124] 2. Experimental Procedure

[0125] (1) Preparation of mixture

[0126] 80g of anhydrous ferrous sulfate, 80g of sodium sulfate and 50g of fluxing salt (LiCl and KCl mixed by mass) are thoroughly mixed to obtain a uniform mixture.

[0127] (2) Wet ball milling treatment

[0128] 1. Preparation of crystallization aids:

[0129] A1: Add 400g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 35℃, and add 2g of ethylenediamine as a catalyst;

[0130] A2: Slowly add 40g of allyl mercaptan over a period of 0.5h, maintain the stirring speed at 150rpm, and keep the reaction at 35℃ for 4h. After the reaction is complete, evaporate under reduced pressure to concentrate to half of the original volume, cool to room temperature and let it stand to crystallize for 12h. Filter and collect the crystals, and dry them under vacuum at 70℃ for 3h to obtain the crystallization aid.

[0131] 2. Ball milling: Under Ar gas protection, add 50g of ethanol and 2g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 10:1), place it in a ball mill for wet ball milling, set the rotation speed to 200r / min, and the ball milling time to 2h.

[0132] (3) Segmented heating and roasting

[0133] The ball-milled mixture was placed into a graphite crucible, and Ar gas (flow rate 100 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 190℃ (200±10℃) and held for 2 hours, then raised to 340℃ (350±10℃) and held for 0.5 hours, then raised to 440℃ (450±10℃) and held for 8 hours, and finally raised to 540℃ (550±10℃) and held for 1 hour. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0134] (4) Washing and drying

[0135] The calcined powder obtained in step (3) was washed twice with ethanol, each time using twice the amount of ethanol as the powder mass; after filtration, the precipitate was placed in an oven and dried at 110℃ (120±10℃) for 6 hours to obtain the dried precursor powder.

[0136] (5) Carbon mixing and high-temperature treatment

[0137] The dried precursor powder was placed under Ar gas protection, and 5g of petroleum coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 590℃ (600±10℃) and kept at that temperature for 3h. The mixture was then cooled to room temperature to obtain highly crystalline Na2Fe2(SO4)3 active powder.

[0138] Comparative Example 3: Low-temperature rapid solid-state synthesis of highly crystalline Na2Fe2(SO4)3 cathode material

[0139] 1. Experimental Materials

[0140] Anhydrous ferrous sulfate (80g, purity ≥99.0%), sodium sulfate (80g, purity ≥99.0%), fluxing salt mixture (LiCl 25g + KCl 25g, mass ratio 1:1), solvent (ethanol 50g), crystallization aid raw materials (4-propenylthioaminourea 60g, anhydrous ethanol 400g, ethylenediamine 2g), amorphous carbon (petroleum coking residue 5g), ball milling beads, Ar gas, ethanol (for washing), graphite crucible.

[0141] 2. Experimental Procedure

[0142] (1) Preparation of mixture

[0143] 80g of anhydrous ferrous sulfate, 80g of sodium sulfate and 50g of fluxing salt (LiCl and KCl mixed by mass) are thoroughly mixed to obtain a uniform mixture.

[0144] (2) Wet ball milling treatment

[0145] 1. Preparation of crystallization aids:

[0146] A1: Add 60g of 4-propenylthioaminourea and 400g of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 35℃, and add 2g of ethylenediamine as a catalyst.

[0147] A2: The stirring rate was maintained at 150 rpm, and the reaction was kept at 35℃ for 4 hours. After the reaction was completed, the mixture was concentrated to 1 / 2 of its original volume by vacuum evaporation, cooled to room temperature and allowed to stand for crystallization for 12 hours. The crystals were collected by filtration and dried under vacuum at 70℃ for 3 hours to obtain the crystallization aid.

[0148] 2. Ball milling: Under Ar gas protection, add 50g of ethanol and 2g of the above crystallization aid to the mixture in step (1), then add ball milling beads (the mass ratio of ball milling beads to mixture is 10:1), place it in a ball mill for wet ball milling, set the rotation speed to 200r / min, and the ball milling time to 2h.

[0149] (3) Segmented heating and roasting

[0150] The ball-milled mixture was placed into a graphite crucible, and Ar gas (flow rate 100 mL / min) was introduced. The mixture was then processed according to the following temperature program: first, the temperature was raised to 190℃ (200±10℃) and held for 2 hours, then raised to 340℃ (350±10℃) and held for 0.5 hours, then raised to 440℃ (450±10℃) and held for 8 hours, and finally raised to 540℃ (550±10℃) and held for 1 hour. The mixture was then allowed to cool naturally to room temperature to obtain calcined powder.

[0151] (4) Washing and drying

[0152] The calcined powder obtained in step (3) was washed twice with ethanol, each time using twice the amount of ethanol as the powder mass; after filtration, the precipitate was placed in an oven and dried at 110℃ (120±10℃) for 6 hours to obtain the dried precursor powder.

[0153] (5) Carbon mixing and high-temperature treatment

[0154] The dried precursor powder was placed under Ar gas protection, and 5g of petroleum coking residue (amorphous carbon) was added and mixed evenly. The mixture was heated to 590℃ (600±10℃) and kept at that temperature for 3h. The mixture was then cooled to room temperature to obtain highly crystalline Na2Fe2(SO4)3 active powder.

[0155] Test method:

[0156] 1. Powder property testing

[0157] Particle size distribution: The volume average particle size D50 was measured using a laser particle size analyzer (Malvern Mastersizer).

[0158] Specific surface area: The specific surface area (m² / g) was determined using the BET nitrogen adsorption method.

[0159] 2. Electrode preparation and electrochemical testing

[0160] Electrode preparation: The active material, acetylene black (conductive agent), and polyvinylidene fluoride (PVDF, binder) were mixed in a mass ratio of 8:1:1. A slurry was prepared using N-methylpyrrolidone (NMP), coated onto aluminum foil, dried in an oven at -120 °C for 12 hours, and then pressed into tablets. The active material mass is approximately 2–3 mg / cm².

[0161] Assemble the half-cell: Sodium metal is used as the negative electrode, active material is used as the positive electrode, polyethylene (PE) is used as the separator, and 1.0 M NaClO4 is used as the electrolyte with EC / DMC = 1:1 (v / v) + 5 wt% VC.

[0162] Cycling and rate testing: Initial charge and discharge at 0.1 C rate within a voltage range of 2.0–4.5 V (vs Na⁺ / Na), followed by rate performance testing at 10 C. Cycling testing was performed 100 times at 1 C.

[0163] Table 1 Test Results

[0164] Average particle size nm Specific surface area m2 / g Initial reversible capacity (0.1 C) mAh / g Capacity retention after 100 cycles (1 C) % Discharge capacity @10C mAh / g Example 1 460 15 110 92.2 71 Example 2 455 17 114 92.5 73 Example 3 445 18 117 92.7 75 Example 4 440 20 120 93.0 77 Comparative Example 1 465 14 103 91.4 67 Comparative Example 2 460 15 108 91.9 70 Comparative Example 3 465 14 106 91.7 69

[0165] In the embodiments of this invention, the average particle size decreased and the specific surface area increased, indicating that the particles were refined and the specific surface area was increased through a low-temperature rapid solid-state process. Regarding electrochemical performance, the initial capacity of the embodiments was higher than that of the comparative example; the capacity retention rate after 100 cycles was better than that of the comparative example; and in terms of rate performance (10 C), the discharge capacity of the embodiments was higher than that of the comparative example, indicating improvements in conductivity, ion migration rate, etc.

[0166] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material, characterized in that, Includes the following steps, measured in parts by weight: (1) Mix 80-100 parts of anhydrous ferrous sulfate, 80-100 parts of sodium sulfate and 50-120 parts of fluxing salt by mass to obtain a mixture; (2) Under the protection of inert gas, add 50-95 parts of solvent and 2-5 parts of crystallization aid to the mixture in step (1), add ball milling beads and perform wet ball milling for 2-6 hours and 200-500 r / min. (3) The ball-milled mixture is loaded into a graphite crucible and heated and held in an inert gas according to the following temperature program: 200±10℃ for 2 h~3 h, then heated to 350±10℃ for 1 h±0.5 h, then heated to 450±10℃ for 8 h~12 h, then heated to 550±10℃ for 1 h~3 h, and then naturally cooled to room temperature; (4) Wash the powder obtained in step (3) twice with ethanol, each time using 2 to 5 times the mass of the powder, filter and dry to obtain the dry precursor powder. (5) Place the dried precursor powder in an inert gas, add 5 to 10 parts of amorphous carbon and mix evenly, heat to 600±10℃ and keep warm for 3 to 5 hours, then cool to room temperature to obtain the final highly crystalline Na2Fe2(SO4)3 active powder.

2. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The purity of the anhydrous ferrous sulfate and sodium sulfate is not less than 99.0%.

3. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The fluxing salt mixture is prepared with a mass ratio of LiCl:KCl = 1:

1.

4. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The inert gas is Ar or He, and the flow rate is 100–300 mL / min.

5. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The solvent is ethanol, acetone, ethylene glycol, or N-methylpyrrolidone.

6. The method for low-temperature rapid solid-state synthesis of a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The crystallization aid is selected from the addition product of 4-propenylthioaminourea and allyl mercaptan under the action of ethylenediamine, and its preparation method is as follows: A1: According to the mass fraction, add 60-90 parts of 4-propenylthioaminourea and 400-600 parts of anhydrous ethanol to the reaction vessel, stir to dissolve, heat to 35-45℃, and add 2-4 parts of ethylenediamine as a catalyst. A2: Slowly add 40-60 parts of allyl mercaptan, controlling the addition time to be 0.5-1h, maintaining the stirring speed at 150-200rpm, and keep the reaction at 35-45℃ for 4-5h; after the reaction is completed, evaporate and concentrate under reduced pressure to 1 / 2 of the original volume, cool to room temperature and let it stand to crystallize for 12-16h, filter and collect the crystals, and dry them under vacuum at 70-90℃ for 3-4h to obtain the target crystallization aid.

7. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The mass ratio of the grinding balls to the mixture is 10:1 to 30:

1.

8. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The drying temperature is 120±10℃, and the time is 6 h to 12 h.

9. The low-temperature rapid solid-state synthesis method for a highly crystalline Na2Fe2(SO4)3 cathode material according to claim 1, characterized in that: The amorphous carbon is selected from petroleum coking residue, coal coking residue, asphalt coking residue, lignin carbonization residue, or corn stalk carbonization residue.

Citation Information

Patent Citations

  • Sodium-ion battery positive pole Na2+2xFe2-x(SO4)3@ carbon composite material and preparing method thereof

    CN105355886A

  • A sodium-ion battery cathode Na2Fe2(SO4)3@alumina composite material and its preparation method

    CN106058251B